An experimental investogation of mode-I interlaminar fracture of composite pipes - REKBI, Fares Mohammed Laid; HECINI, Mabrouk; KHECHAI, Abdelhak (University of Eloued جامعة الوادي, 2018)
A common industrial production process for composites is filament winding, widely used for the production of axially symmetric components. In these composite components, delamination is a predominant failure mechanism. The current work focused on investigating the possibilities of determining the effect of the initial crack on the interlaminar fracture toughness GIC and the compliance C, which enable the investigation of resistance curve (R-curve) behavior for mode I delamination growth. For this purpose, DCB specimens with stacking sequence of [±50]6 and initial crack length of a0=33, 37, 59 and 70 mm are manufactured as a composite pipe by the filament winding process. In order to evaluate the critical energy release rate in mode I, fracture tests are conducted on these specimens. Results show that the magnitudes of initiation delamination toughness (GIC-init) are constant in a range of the initial crack length to the DCB specimen 33≤a0≤70 mm. Finally, GIC-init measurements are compared with those from the Finite Element (FE) models. The numerical results from the FE models are in good agreement with the experimental results.
International Symposium on Mechatronics and Renewable Energies El-Oued 10- 11 December 2018
Keywords: Critical energy release rate, propagation energy release rate, filament wound composite, DCB specimen, R-curve